Ledgerbook entry - unknown:::Creator::::::::::::
Steinbeck's handwritten ledgerbook entry of stories completed in the summer of 1934 with accompanying notes. 'The Promise (refused N.A.R.),' 'The Leader of the People,' 'How Edith McGillcuddy met R.L.S. (withdrawn)', 'The Raid,' 'The Harness,' 'The White Quail,' 'Flight,' 'Johnny Bear,' 'The Vigilante.' RESTRICTED USE